Novel Point Mutations in Frataxin Gene in Iranian Patients with Friedreich’s Ataxia - HEIDARI*, Mohammad Mehdi; KHATAMI, Mehri; POURAKRAMI, Jafar (Iranian Journal of Child Neurology, 2014)
How to Cite This Article: Heidari MM , Khatami M, Pourakrami J. Novel Point Mutations in Frataxin Gene in Iranian Patients with Friedreich’s Ataxia. Iran J Child Neurol. 2014 Winter; 8(1):32-36. Objective Friedreich’s ataxia is the most common form of hereditary ataxia with autosomal recessive pattern. More than 96% of patients are homozygous for GAA repeat extension on both alleles in the first intron of FXN gene and the remaining patients have been shown to be heterozygous for a GAA extension in one allele and point mutation in other allele. Materials & Methods In this study, exons of 1, 2, 3, and 5 of frataxin gene were searched by single strand conformation polymorphism polymerase chain reaction (PCR-SSCP) in 5 patients with GAA extension in one allele. For detection of exact mutation, samples with band shifts were sent for DNA sequencing. Results Three novel point mutations were found in patients heterozygous for the GAA repeat expansion, p.S81A, p.Y123D, and p.S192C. Conclusion Our results showed that these point mutations in one allele with GAA extension in another allele are associated with FRDA signs. Thus, these results emphasize the importance of performing molecular genetic analysis for point mutations in FRDA patients. References: Delatycki MB, Williamson R, Forrest SM. Friedreich ataxia: an overview. J Med Genet 2000;37(1):1-8. Harding AE, Zilkha KJ. ‘Pseudo-dominant’ inheritance in Friedreich’s ataxia. J Med Genet 1981;18(4):285-7. Schulz JB, Boesch S, Burk K, Durr A, Giunti P, Mariotti C, et al. Diagnosis and treatment of Friedreich ataxia: a European perspective. Nat Rev Neurol 2009;5(4):222-34. Campuzano V, Montermini L, Lutz Y, Cova L, Hindelang C, Jiralerspong S, et al. Frataxin is reduced in Friedreich ataxia patients and is associated with mitochondrial membranes. Hum Mol Genet 1997;6(11):1771-80. Sharma R, De Biase I, Gomez M, Delatycki MB, Ashizawa T, Bidichandani SI. Friedreich ataxia in carriers of unstable borderline GAA triplet-repeat alleles. Ann Neurol 2004;56(6):898-901. Durr A, Cossee M, Agid Y, Campuzano V, Mignard C, Penet C, et al. Clinical and genetic abnormalities in patients with Friedreich’s ataxia. N Engl J Med 1996;17;335(16):1169-75. Filla A, De Michele G, Cavalcanti F, Pianese L, Monticelli A, Campanella G, et al. The relationship between trinucleotide (GAA) repeat length and clinical features in Friedreich ataxia. Am J Hum Genet 1996;59(3):554-60. Lamont PJ, Davis MB, Wood NW. Identification and sizing of the GAA trinucleotide repeat expansion of Friedreich’s ataxia in 56 patients. Clinical and genetic correlates. Brain 1997;120 ( Pt 4):673-80. Montermini L, Richter A, Morgan K, Justice CM, Julien D, Castellotti B, et al. Phenotypic variability in Friedreich ataxia: role of the associated GAA triplet repeat expansion. Ann Neurol 1997;41(5):675-82. Monros E, Molto MD, Martinez F, Canizares J, Blanca J, Vilchez JJ, et al. Phenotype correlation and intergenerational dynamics of the Friedreich ataxia GAA trinucleotide repeat. Am J Hum Genet 1997;61(1):101-10. Zuhlke CH, Dalski A, Habeck M, Straube K, Hedrich K, Hoeltzenbein M, et al. Extension of the mutation spectrum in Friedreich’s ataxia: detection of an exon deletion and novel missense mutations. Eur J Hum Genet 2004;12(11):979-82. Heidari MM, Houshmand M, Hosseinkhani S, Nafissi S, Scheiber-Mojdehkar B, Khatami M. A novel mitochondrial heteroplasmic C13806A point mutation associated with Iranian Friedreich’s ataxia. Cell Mol Neurobiol 2009;29(2):225-33. Heidari MM, Houshmand M, Hosseinkhani S, Nafissi S, Scheiber-Mojdehkar B, Khatami M. Association between trinucleotide CAG repeats of the DNA polymerase gene (POLG) with age of onset of Iranian Friedreich’s ataxia patients. Neurol Sci 2008; 29(6):489-93. Heidari MM, Houshmand M, Hosseinkhani S, Nafissi S, Khatami M. Complex I and ATP content deficiency in lymphocytes from Friedreich’s ataxia. Can J Neurol Sci 2009;36(1):26-31. Campuzano V, Montermini L, Molto MD, Pianese L, Cossee M, Cavalcanti F, et al. Friedreich’s ataxia: autosomal recessive disease caused by an intronic GAA triplet repeat expansion. Science 1996;271(5254):1423-7. Sambrook J, Russel DW. Chapter 13: Detection of Mutations by Single-strand Conformational Polymorphism and Heteroduplex Analysis. Molecular cloning: a laboratory manual. 3eded. New York: Cold Spring Harborn Laboratory Press; 2001. P.49-59. Kyte J, Doolittle RF. A simple method for displaying the hydropathic character of a protein. J Mol Biol 1982;157(1):105-32. Harding AE, Hewer RL. The heart disease of Friedreich’s ataxia: a clinical and electrocardiographic study of 115 patients, with an analysis of serial electrocardiographic changes in 30 cases. Q J Med 1983;52(208):489-502. Cavalier L, Ouahchi K, Kayden HJ, Di Donato S, Reutenauer L, Mandel JL, et al. Ataxia with isolated vitamin E deficiency: heterogeneity of mutations and phenotypic variability in a large number of families. Am J Hum Genet 1998;62(2):301-10. Anheim M, Mariani LL, Calvas P, Cheuret E, Zagnoli F, Odent S, et al. Exonic deletions of FXN and early-onset Friedreich ataxia. Arch Neurol 2012;69(7):912-6. Li H, Gakh O, Smith DYt, Ranatunga WK, Isaya G. Missense mutations linked to friedreich ataxia have different but synergistic effects on mitochondrial frataxin isoforms. J Biol Chem 2013;288(6):4116-27. Evans-Galea MV, Corben LA, Hasell J, Galea CA, Fahey MC, du Sart D, et al. A novel deletion-insertion mutation identified in exon 3 of FXN in two siblings with a severe Friedreich ataxia phenotype. Neurogenetics 2011;12(4):307-13.